A survey of college and university libraries in Region I its implications to the Private Higher Education (PHE) Library Standards - Seng, Olga G.; Estavillo, Corazon C.; Nera, Corazon M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1981)
The major purposes of this study are to investigate, assess, and analyze the problems which exist in and impede the development of private college and university libraries in Region I against the PHE Tentative Library Standards and to make recommendations for their improvement and development.
The procedures followed include (1) the selection of the private institutions and distribution of the questionnaire; (2) on-site visits to some of the institutions to check the reliability of responses; and (3) organization and analysis of the data against the PHE Tentative Library Standards.
The questionnaire contained fifty-five questions classified under six major categories: general information about the school, library resources, library physical facilities and equipment, organization and administration, library collection, library budget, and library personnel.
The study was limited to data relating to ten private institutions in Region I during the school year 1978-1979. Analysis of the data revealed that the status of the library facilities and equipment, organization and administration, library collection, library budget and personnel in the ten schools is almost deplorable. There are some institutions that are singularly outstanding in these general conditions but for such instances there is a considerable number that fall far below the standards set by the PHE. Although majority of the institutions are in a deplorable state, significant evidences show that there is proper organization of their library collection and are systematically arranged for efficient identification and retrieval when needed.
Specific recommendations such as improving the lighting and ventilation of reading rooms, increasing the library budget and hiring professional librarians for each area of need in library physical facilities and equipment, organization and administration, library collection, budget and personnel are set down in order that these schools may meet the standards and thus lead to their improvement.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Libraries, University and College -- Philippines -- Region I; Libraries -- Standards